A Study of Strategies to Achieve Proper N95 Respirator Use by Regular N95 Respirator - Tontiruck, Nuttakarn; Krisorn, Phanumas; Chaiear, Naesinee; Aupongkaroon, Thanaphoom (Biomedical Sciences and Clinical Medicine, 2025)
Objective To explore different strategies for achieving proper use of N95 respirators by hospital staff, including viewing the donning process in a mirror, receiving assistance from a Buddy during donning, and using a bouffant cap to cover the hair after donning an N95 respirator. This study evaluated the fit factor, the time required for donning a respirator, and the practical usability of each strategy. Methods This quasi-experimental study involved 60 healthcare workers. Demographic and medical information were collected using Occupational Safety and Health Administration (OSHA) compliant questionnaires. Facial dimensions were measured and classified into three face-size groups according to the NIOSH bivariate panel. Participants practiced one of four different N95 respirator donning strategies after watching a training video: using a mirror, receiving Buddy assistance, and using a bouffant cap. A quantitative fit test (QNFT) was conducted before and after practicing each strategy following a modified OSHA protocol. After completing each of the strategies, participants indicated their preferred donning method. They were subsequently randomly divided into three groups to further practice one of the strategies, with repeated QNFTs to ensure consistency. Results Post video training, participants had a higher fit factor (FFs) (median, IQR) (113.50 [48.50, 200]) and an increased passing rate (61.67%) on the fit test compared to no training which had an FF of 65.50 [18.50, 118.50]) and a passing rate of 25.00%. Practice with the Buddy and Mirror strategies resulted in significantly higher FFs for small, medium, and large face sizes. The Bouffant cap strategy showed significantly higher FF than post video training alone for small face sizes: (102 [50.5, 143]) and (50 [18, 108]), respectively. Conclusions The study found significant differences in FF for different facial sizes, with participants having medium and large face sizes achieving higher FFs compared to those with small face sizes. For individuals with small face sizes, FF improved significantly post video training using alternative strategies (Mirror, Buddy, and Bouffant cap) compared to no training. Using a mirror during donning allowed wearers to inspect the mask fit more effectively, while the Buddy strategy proved more efficient in identifying and addressing leaks compared to self-checking.